A Literature Review of the Efficacy of Repetitive Transcranial Magnetic Stimulation on Epilepsy - Tavakoli, Hassan; Heidarpanah, Arsalan (Iranian Journal of Child Neurology, 2023)
Repetitive transcranial magnetic stimulation (rTMS), often recognized as a safe and tolerable method with promising therapeutic potential for the treatment of a variety of neurological disorders, has been extensively studied by medical engineering scientists in recent decades. Epilepsy has always been one of the vital foci in the therapeutic role of rTMS, especially its low-frequency type. However, various reports, clinical trials, and review articles published in recent years have yielded conflicting results regarding the efficacy and sideeffects of rTMS in patients. In this review article, reviewing studies published from January 2000 to October 2021, we examined the efficacy and side effects of rTMS with a specific look at its therapeutic applications in epilepsy. Our study indicates promising results in the clinical application of this technique for patients with epilepsy. Among other things, it has the ability to reduce interictal epileptic abnormalities, does not interfere with neuropsychological function in normal people, does not worsen cognitive function and even improves Stroop function, rarely has serious side effects such as seizures and psychotic symptoms, has low risk in children as adults, and has potential for improving suicidalideation. Despite some limitations in this study, including the small number of studies performed and the heterogeneity among studies, this review article suggests significant rtMS potentials in improving the complications of epilepsy. Our review also showed that the reported side effects of using this technique are not very common. Therefore we can recommend further use of this technique as a promising tool in clinical research.